2014
DOI: 10.1103/physrevstab.17.051303
|View full text |Cite
|
Sign up to set email alerts
|

Electron injection and emittance control by transverse colliding pulses in a laser-plasma accelerator

Abstract: A method to inject electron beams with controllable transverse emittances in a laser-plasma accelerators is proposed and analyzed. It uses two colliding laser pulses that propagate transversely to the plasma wave. For colliding pulses with equal frequencies, a beam with very low emittance is generated when the collision is close to the density peak of the plasma wave. Electrons near the axis are accelerated longitudinally by the ponderomotive force of the colliding pulses, accelerated transversely by the beat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…4(b) it can be found that the e beam is self-injected into the second bucket longitudinally, which leads to small transverse momentum and transverse position. This longitudinal self-injection mechanism will lead to a low transverse emittance in the acceleration process 8,28 . After being seeded into the base of the first bucket, the e beam experiences the highest accelerating field and maintains a small transverse momentum for re-acceleration, as shown in Fig.…”
Section: Two-dimensional Pic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(b) it can be found that the e beam is self-injected into the second bucket longitudinally, which leads to small transverse momentum and transverse position. This longitudinal self-injection mechanism will lead to a low transverse emittance in the acceleration process 8,28 . After being seeded into the base of the first bucket, the e beam experiences the highest accelerating field and maintains a small transverse momentum for re-acceleration, as shown in Fig.…”
Section: Two-dimensional Pic Simulationsmentioning
confidence: 99%
“…To realize the practical applications of LWFAs 19,20,26 , low-emittance e beams 27,28 are required specially to minimize the degradation over long-distance propagation. The transverse emittance, a nontrivial experimental parameter of high-energy e beams, needs to be measured.…”
Section: Introductionmentioning
confidence: 99%
“…This outstanding feature promises a dramatic miniaturisation of future accelerators and an according reduction of costs. Present efforts within the field of plasmabased accelerators are directed towards the generation of a large number of electrons, occupying a small (transverse) phase-space volume [34][35][36][37][38], and the subsequent acceleration to great energies while maintaining the populated volume [39][40][41]. The transverse quality of a beam is quantified by the transverse phase-space emittance (see e.g.…”
Section: Beam Emittance In Plasma-based Acceleratorsmentioning
confidence: 99%
“…The injection length of self-injection is typically a few hundreds of microns [15,23], and the divergence of injected electrons is typically a few milliradians [33][34][35]. Several controlled injection schemes were proposed, such as the density transition injection [36][37][38][39], multipulse colliding injection [40][41][42][43][44] and ionization injection [45][46][47][48][49][50][51][52][53][54], but the production of GeV electron beam with narrow energy spread (≲0.5%) remains to be challenging.…”
Section: Introductionmentioning
confidence: 99%